Consensus on the therapeutic management of rosacea - Brazilian Society of Dermatology, - Clivia Maria Moraes de Oliveira; Luiz Mauricio Costa Almeida; Renan Rangel Bonamigo; Carla Wanderley Gayoso de Lima; Ediléia Bagatin (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Rosacea is a chronic inflammatory disease of the skin, relatively more frequent in women over 30 with a low phototype and proven genetic predisposition. Although its etiology is unknown and possibly multifactorial, the immunological abnormality, associated with neurovascular dysregulation and triggering factors, are important elements in its pathophysiology, which lead to the main changes of inflammation, vasodilation, and angiogenesis that are responsible for the clinical manifestations. Despite the lack of cure, numerous therapeutic options are available for the different clinical presentations of the disease, with satisfactory responses. Objective: To reach a consensus, with recommendations from experts, on the therapeutic management of rosacea suitable to the Brazilian setting. Methods: The study was conducted by five specialized dermatologists from university centers, representatives of the different Brazilian regions, with experience in rosacea, who were appointed by the Brazilian Society of Dermatology. Based on the adapted DELPHI methodology, the experts contributed through an updated bibliographic review of the scientific evidence, combined with personal experiences. Results: The group of experts reached a consensus on the relevant aspects in the therapeutic management of rosacea, providing information on epidemiology, pathophysiology, triggering factors, clinical condition, classification, quality of life, and comorbidities. Consensus was defined as approval by at least 90% of the panel. Conclusion: Despite the impossibility of cure, there are several therapeutic alternatives specific to each patient that provide excellent results, with chances of total improvement and long periods of remission, promoting a positive impact on quality of life. This consensus provides detailed guidance for clinical practice and therapeutic decisions in rosacea.